RHEOLOGY OF FERRO-FLUIDS AND THEIR APPLICATION IN SPACE TECHNOLOGY - Khusniddinov Fakhriddin Shamsiddinovich; Sultonova Feruza Bobomurodovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article provides an in-depth analysis of the rheological properties of ferrofluids and their applications in space technology. The study then examines the rheological characteristics, changes under the influence of magnetic fields, and practical applications. The article also highlights research by Uzbek and other regional scholars, empirical findings, and contemporary scientific debates and challenges.